A Descriptive Study On Contraceptive Practices Among Mothers In Belhara Vdc Of Dhankuta District, Nepal - Rayamajhi, Rajam Bikram; Ghimire, A; Niraula, SR; Budhathoki, SS; Khanal, VK; Pokharel, PK (Journal of Chitwan Medical College, 2014)
Nepal, having a predominance of patriarchal society, contraceptive is used by of the females in most cases. Utilization of the family planning services is vital for reduce maternal and neonatal morbidity and mortality in an underdeveloped country like ours. The objective of the study was to assess the awareness and practices of various modes of family planning methods present among the mothers in Belhara VDC of Dhankuta district. A descriptive cross sectional study was carried out among 291 mothers with door to door visit using random sampling. 92% of the participants were aware about the use of family planning methods but only 87% of them were current family planning users and Depo (92.6%) was found to be the most popular mode of contraception among users. Despite vigorous social marketing about family planning methods, about 8% of the women weren’t aware about it and Depo (92.6%) was found to be the most popular mode of contraception with husband’s desire (84.7%) being the main reason behind the uptake of the service. Journal of Chitwan Medical College 2013; 3(4); 34-37 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9552